Public Opinion about European Researchers’ Night on Climate Change and Polar Science in Türkiye - Nasıh Sarp Ergüven; Fatma Mızıkacı; Tuğba Güner Demir; Pelin Taşkın (e-Kafkas Eğitim Araştırmaları Dergisi)
The European Researchers' Night is an annual event held across Europe on the last Friday of September, with the primary goal of promoting public recognition of scientists, disseminating information about the real-world impact of their research, inspiring young people to pursue careers in science, and raising awareness about research and innovation activities. In 2022, European Researcher’s Night focused on climate change and polar science in Istanbul and Gaziantep provinces. The central aim was to enhance public awareness of polar regions and global climate change, as well as to facilitate the acknowledgment of researchers and their work by the general public. This study examined the opinions of participants who attended these events, including 221 primary school students, 687 secondary school students, 525 high school students, and 319 adults. Utilizing a mixed-method approach, participant opinions were collected through both quantitative questionnaires and qualitative interviews conducted concurrently during the events. The results revealed overwhelmingly positive feedback from all participants regarding the events, with unanimous support for the continuation of such engaging public outreach initiatives. In conclusion, these events serve as effective channels for communicating scientific research with the public and underscore the importance of research extending beyond the confines of research communities.